Proportional cancer incidence according to selected sites: comparison between residents in the City of S. Paulo, Brazil: Japanese and Brazilian/Portuguese descent Incidência proporcional por câncer: comparação entre residentes no Município de São Paulo de diferentes origens: japonesa e brasileira - José Maria Pacheco de Souza; Sabina Léa Davidson Gotlieb; Moacyr Lobo da Costa Júnior; Ruy Laurenti; Antonio Pedro Mirra; Shoichiro Tsugane; Shaw Watanabe (Revista de Saúde Pública, 1991)
The percentual distributions of selected sites of cancer cases according to origin, sex and age are compared. Data were obtained from the Registry of Cancer of S. Paulo (School of Public Health of the University of S. Paulo, Brazil). The reference period for inhabitants of Japanese descent was 1969/78 and for those of Brazilian descent, the period was 1969/75. Standardized Proportionate Incidence Ratios (SPIR) with approximate 95% Confidence Intervals (CI) were evaluated using age specific Incidence Ratios of S. Paulo, 1973, as standards. The results agree with findings of previous works on mortality, but show different patterns according to origin. The well known fact that some sub-groups of a population may be different from the overall group is once again brought to the fore. Attention should be drawn to the differences detected for stomach, skin and prostate, in males, and for stomach, skin, cervix and uterus in females. São comparadas as distribuições percentuais dos casos de câncer de algumas localizações anatômicas segundo país de nascimento, sexo e idade. Os dados foram coletados no Registro de Câncer de São Paulo da Faculdade de Saúde Pública da USP, referentes aos períodos 1969-1978, para os japoneses, e 1969-1975, para os brasileiros. Razões padronizadas de incidência proporcional e respectivos intervalos com 95% de confiança foram calculados, usando como padrão a incidência proporcional específica por idade de São Paulo, em 1973. Os resultados, consistentes com trabalhos anteriores relativos à mortalidade, mostraram haver possíveis padrões distintos de incidência de câncer em japoneses e brasileiros. Chamou atenção para o fato de que alguns sub-grupos de uma população apresentam comportamentos diferentes e, no presente caso, principalmente quanto à incidência de cânceres de estômago, próstata, pele, em homens, e estômago, pele, colo uterino e útero, em mulheres.